Gastrointestinal tract pH and gizzard morphometry of Finishing Ross 308 broiler chickens fed diets containing lactic acid bacteria probiotics - Guluwa, L. Y.; Wumnokol, D.P.; Dantayi, R. J.; Gulukun, E. Z.; Latu, M. A.; Dalokom, C. Y.; Gyang, I. Y. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
Indigenous Lactic acid bacteria probiotic (ILABP) considered in this study are friendly microbes or lactic acid bacteria isolated from the feaces and gastrointestinal tract of local chickens at National Veterinary Research Institute Vom, Nigeria, that are known to have remarkable benefit in animal agriculture. Indigenous Lactic acid bacteria are natural occurring lactic acid bacteria which inhabits the gastrointestinal tract of chickens as targeted environment. Fifty six (56) days feeding trial involving 200 broiler chickens was carried out at the poultry Unit of Plateau State College of Agriculture, Garkawa to evaluate the influence of Indigenous Lactic acid bacteria probiotic on their gastrointestinal pH and gizzard morphometry. Five experimental diets were formulated using least cost feedwin software to incorporate Indigenous Lactic acid bacteria with minimum presence of 0.0 x 108 CFU as treatment 1 and other treatments were 7.2 x 108 CFU L. plantarum, 4.2 x 107 CFU Pediococcus pentosaceous, 1.8 x 108 CFU L. fermentum and combination of L. plantarum, Pediococcus pentosaceous and L. fermentum per ml as treatments 2, 3, 4 and 5, respectively. The birds were assigned to these five treatments with 40 birds per treatment replicated four times with ten birds in a completely randomized design. Results of gastrointestinal tract pH parameters revealed no significant changes in the crop, gizzard, small intestine, large intestine and ceacum except proventriculus. Gizzard pH of 3.00 – 3.60 supported the proliferations of lactobacillus species by preventing bacteria entering into the distal intestinal tract due to its low pH. The non significant differences for small and large intestine pH may be an indicator for microbial balance for nutrient absorption for digestion of feed nutrients. This presents ILABP as a promising feed additive in poultry nutrition.  Broiler chickens fed mixture of IMOs L. plantarum, Pediococcus pentosaceous and L. fermentum improves gizzard % LW and gizzard thickness for mechanical breakdown of feed to aid uniform mixing, solubility and absorption of nutrients at the small intestine. In conclusion, combination of different beneficial microbes as probiotics (T5) (L. plantarum, Pediococcus pentosaceous and L. fermentum) could be used in poultry nutrition to promote gizzard functionality.